1993
DOI: 10.1093/nar/21.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophic effects of point mutations in yeast tRNAAspon the base modification pattern

Abstract: The base-modification pattern has been studied in several synthetic variants of yeast tRNA(Asp) injected into Xenopus laevis oocytes. Certain point mutations in the D-stem and the variable loop of the tRNA led to considerably decreased levels of m1G37, psi 40 and Q34/manQ34 in the anticodon stem or loop and an increased rate of synthesis for m5C49 in the T-stem. The formation of m2G6 in the aminoacyl-stem was not affected in any of the tRNA-variants. Thus, mutations in one part of the tRNA-molecule can have lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…It is possible that one or more other steps in tRNA metabolism provide the selective pressure for the conserved nucleotides. Indeed, several of the same mutations studied in this work have been found to have substantial effects in other steps of tRNA metabolism including tRNA modification (Drabkin and RajBhandary, 1985;Edqvist et al, 1993), RNase P activity (Bear et al, 1988;Thurlow et al, 1991) and tRNA splicing (Greer et al, 1987;Mattocia et al, 1988;Reyes and Abelson, 1988). Another possibility is that most of the selective pressure for the conserved sequences does indeed come from the ribosome, but the biochemical effects are quite small.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is possible that one or more other steps in tRNA metabolism provide the selective pressure for the conserved nucleotides. Indeed, several of the same mutations studied in this work have been found to have substantial effects in other steps of tRNA metabolism including tRNA modification (Drabkin and RajBhandary, 1985;Edqvist et al, 1993), RNase P activity (Bear et al, 1988;Thurlow et al, 1991) and tRNA splicing (Greer et al, 1987;Mattocia et al, 1988;Reyes and Abelson, 1988). Another possibility is that most of the selective pressure for the conserved sequences does indeed come from the ribosome, but the biochemical effects are quite small.…”
Section: Discussionmentioning
confidence: 72%
“…It is likely that these two categories of enzymes achieve their substrate specificity quite differently. In the case of many tRNA synthetases (Pallanck and Schulman, 1992;Giege et al, 1993) and several modifying enzymes (Bjork, 1992;Lee et al, 1992;Edqvist et al, 1993), it is known that certain specific nucleotides unique to the substrate tRNAs are essential to the specificity. It is often possible to transplant these 'recognition nucleotides' into tRNAs that are not substrates and thereby convert them into substrates (Normanly et al, 1986;Sampson et al, 1989;Schulman and Pelka, 1988;Pallanck and Schulman, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Spectrophotometric assays for respiratory chain enzymes, however, showed a significant decrease in complex I, III and IV activities, though less severe than in patient 1. Base-pair disruptions in the D-stem ofyeast tRNAM'P (the same region of the 3256 mutation in the mitochondrial tRNAL(UUR)) had several deleterious effects on tRNA maturation, including decreased aminoacylation (49) and decreased levels ofphysiologically normal chemical modifications (e.g., methylation or pseudouridine formation) in specific nucleotides (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, tRNA modifying enzymes catalysing the formation of some other modi®ed nucleosides present in the anticodon region (including the enzymes for the formation of m 1 G37, wybutosine(yW37) and queuosine(Q34)) recognise not only a speci®c nucleotide sequence within the anticodon loop, close to the target nucleotide, but also more general features of the tRNA molecule (Grosjean et al, 1987(Grosjean et al, , 1990. The major determinant for the tRNA (m 5 U54)methyltransferase, which catalyses the formation of 5-methyluridine (m 5 U) in position 54 of all tRNA species in E. coli and S. typhimurium, requires sequences in both the T-stem and in the Tloop (Gu & Santi, 1991 2 G), are not only the nearby nucleotides but also the presence of the two D stem base-pairs (C11 Á G24, G1ÁC25) as well as the three-dimensional structure (Edqvist et al, 1992(Edqvist et al, , 1993(Edqvist et al, , 1994. By injecting various unmodi®ed yeast tRNA Asp into Xenopus oocytes and following the formation of different modi®ed nucleosides, Grosjean and co-workers (Grosjean et al, 1996) suggested that there are two classes of oocyte tRNA modifying enzymes.…”
Section: Introductionmentioning
confidence: 99%